2019
DOI: 10.1093/cid/ciz050
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Effectiveness of Azithromycin and Doxycycline in Uncomplicated Rectal and Vaginal Chlamydia trachomatis Infections in Women: A Multicenter Observational Study (FemCure)

Abstract: We demonstrated that in 416 women attending a sexually transmitted infection clinic, microbiological cure was low in azithromycin-treated (78.5%) compared with doxycycline-treated (95.5%) rectal chlamydia; microbiological cure in vaginal chlamydia was high for both treatment types (93.5% and 95.4%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 31 publications
1
43
0
Order By: Relevance
“…Recently, our study groups showed a borderline significant association (P = 0.054) between lower vaginal Cq values, i.e. likely higher CT loads, and not reaching microbiological cure for vaginal CT in women treated with azithromycin [32]. Therefore, some women with concurrent vaginal and (untested) anorectal infections in our study may not be microbiologically cured when treated with azithromycin as they tend to have lower Cq values and therefore potentially higher CT loads [32].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, our study groups showed a borderline significant association (P = 0.054) between lower vaginal Cq values, i.e. likely higher CT loads, and not reaching microbiological cure for vaginal CT in women treated with azithromycin [32]. Therefore, some women with concurrent vaginal and (untested) anorectal infections in our study may not be microbiologically cured when treated with azithromycin as they tend to have lower Cq values and therefore potentially higher CT loads [32].…”
Section: Discussionmentioning
confidence: 99%
“…(8) We cannot entirely rule out contamination of swabs during sampling, for example, contamination of a rectal swab with vaginal secretions, despite clear written and visual instructions. (9) In the FemCure study sample, women with high education, without a previous STI or non-Western migrant background were under-represented compared with CT infected STI clinic women 27. However, these characteristics were not associated with clearance overall, and therefore, we think that these differences do not impact the internal validity of the study.…”
Section: Discussionmentioning
confidence: 94%
“…In clinical practice, most women remain rectally untested, missing two-thirds of rectal CT infections when diagnosing vCT 24 25. It may be a problem when these rectally untested (but rCT positive) women are treated with azithromycin for their vCT, as azithromycin is less effective than doxycycline for rCT 26 27. In some of the Dutch STI clinics, and in some international guidelines, universal doxycycline treatment for CT infections in women has been adopted, potentially tackling the aforementioned issue.…”
Section: Discussionmentioning
confidence: 99%
“…Four weeks after treatment, 97.2% of women were negative for oropharyngeal CT. Proportions of cure were similar to those in azithromycin-treated vaginal CT (93.5% (95% CI 90.1% to 96.1%)), in doxycycline-treated vaginal CT (95.4% (95% CI 90.9% to 98.2%)) and in doxycycline-treated rectal CT (95.5% (95% CI 91.0% to 98.2%)); and higher than in azithromycintreated rectal CT (78.5% (95% CI 72.6% to 83.7%)). 17 One woman was positive at all follow-up visits until week 12; she had oropharyngeal viable CT at week 0 and was untested at week −1; she reported receptive oral sex during follow-up.…”
Section: Discussionmentioning
confidence: 97%
“…18 The proportion of positive women with viable oropharyngeal CT was 26.1% (12/46), which is lower than proportions of viable CT that we observed in vaginally (94.0%-96.4%) and in rectally CT-infected women (58.0%-66.5%). 17 Although the proportion with viable oropharyngeal CT is relatively small, it may represent relevant infections for ongoing transmission to a sexual partner via oral sex, 19 but possibly also to the own rectal site, via the gastrointestinal canal. 20 After treatment, following >425 women until week 12, only few women tested positive and most only at a single time point.…”
Section: Discussionmentioning
confidence: 99%